The Role of Prostaglandins in the ADP-Induced Aggregation of Rabbit Platelets Shown by the Use of 15-Hydroxyprostaglandin Dehydrogenase - Wallis, Robert B (Thrombosis and Haemostasis, 1978)
The initial shape change and subsequent aggregation of platelets in citrated rabbit platelet-rich plasma caused by ADP in vitro was inhibited by 15-hydroxyprostaglandin dehydrogenase. This inhibition was NAD-dependent and was also seen when shape change and aggregation were initiated by sodium arachidonate or by collagen. The aggregation of gel-filtered rabbit platelets by thrombin was not, however, affected by removal of 15-hydroxyprostaglandins.Indomethacin was found to inhibit ADP-induced aggregation but at a concentration (250 μM) much higher than that required to inhibit collagen-induced aggregation. Moreover the platelet release reaction had not taken place 3 min after ADP stimulation. The direct role 15-hydroxyprostaglandin production in ADP-induced aggregation of rabbit platelets is proposed. The involvement of 15-hydroxyprostaglandins in platelet aggregation caused by other inducers is also discussed.